Analisis Rantai Pasok Komoditi Kedelai pada Koperasi Produsen Tempe Tahu Indonesia (KOPTI) Kota Bandung - CHRISTIAN, LOUIS; AMBARAWATI, I GUSTI AGUNG AYU; DEWI, RATNA KOMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.2, Desember 2023, 2023)
Supply Chain Analysis of Soybean at the Cooperative of Indonesian Tempe and Tofu Producers in Bandung (KOPTI Kota Bandung).  KOPTI Kota Bandung is one of many parties who doing supply chain activity of the import soybean in Bandung City. The objectives of this study are to analyze mechanism of the soybean supply chain including product, financial, and information drives from KOPTI to downstream consumers and to calculate margin, profit, and efficiency from the chain. Respondents of this study were staff of KOPTI Kota Bandung, selling services unit of KOPTI ( Unit Pelayanan/UP ), retailers, and downstream consumers that were selected by snowball and purposive sampling technique, totaling 47 persons. Data analysis used in this study covered qualitative and quantitative methods. The qualitative was used to analyze the supply chain scheme while the quantitative was used to analyze margin, profit of actors, and efficiency of the supply chain of soybean in February 2022. Data collected in this study was conducted by survey and interviews. Results of the study show that there are 4 streams of the soybean supply chain, 1) KOPTI – downstream consumers, 2) KOPTI – UP – downstream consumers, 3) KOPTI – retailers – downstream consumers, 4) KOPTI – UP – retailers – downstream consumers. Based on the study’s result, all the soybean supply chains at KOPTI Kota Bandung are efficient, shown by the value were less than the required efficient criteria. The most efficient soybean supply chain was the first stream, KOPTI – downstream consumers with the efficient value of 0.86%, distribution margin was Rp 417.00/kg, fully received by KOPTI, and the profit received was Rp 322.00/kg. On the other hand, the most used soybean supply chain was the second stream with 65.41% of total KOPTI’s volume of soybean distribution. In order to increase the volume of soybean distribution in the first stream, KOPTI Kota Bandung is sugessted to consider the policy of the minimum purchased by the downstream consumers. With the intention of preventing the fluctuated soybean’s price, KOPTI Kota Bandung is suggested to increase options for other suppliers either from import or domestics (local farmers).